An efficient video slice encryption scheme and its application - Qinyou Huang; Luping Wang; Jie Chen (Cybersecurity)
Abstract With the widespread application of multimedia data in cloud computing environments, ensuring the security and privacy of video content has become a pressing challenge. Traditional encryption methods have limitations; for instance, naive encryption algorithms and selective encryption can protect video content, but they struggle to balance codec compatibility and security. Full encryption algorithms have higher security compared to selective encryption, though they compromise time efficiency. Despite encryption techniques being employed to safeguard video content, there remain concerns about the security of encrypted videos, especially for highly confidential data. Furthermore, contemporary encryption methods often involve re-encoding and decoding processes, which adversely impact video processing speed. To address this issue, we propose a novel video security encryption scheme that optimally balances encryption speed and security. We introduce a scheme for video fragmentation, design corresponding sorting and merging algorithms, and construct a video transmission framework compatible with this scheme. Secondly, to validate the security of the scheme, we reduce its security to an NP problem and calculate the decryption time complexity, thereby demonstrating its security. Finally, experimental comparisons confirm the efficiency advantage of our scheme in processing large video files. Compared to traditional video encryption techniques, our scheme demonstrates faster overall processing speed and enhanced security when handling large video files. In summary, our scheme achieves a higher level of security while greatly preserving the efficiency of encryption and decryption, and the security foundation relies on cryptography.